Cultural and Religious Dimensions of Career Search Efficacy: A Qualitative Study of Vocational High School Students - Asriyana Asriyana; DYP Sugiharto; Sunawan Sunawan; Heru Mugiarso (Bulletin of Counseling and Psychotherapy, 2025)
This study explores how cultural and religious values shape the career search efficacy of vocational high school students (SMK) in Banda Aceh, Indonesia. Using a qualitative exploratory-descriptive approach, data were collected through semi-structured interviews and focus group discussions (FGDs) involving students and guidance counselors. The findings reveal that career search efficacy is deeply embedded within Acehnese cultural norms, including Islamic principles, familial decision-making (musyawarah), and informal social interactions such as coffee shop discussions. The analysis identified four key dimensions of culturally influenced career search efficacy: career exploration, interview efficacy, networking efficacy, and personal exploration. These dimensions illustrate that students' career development is not only an individual process but also one that is shaped by community values and spiritual beliefs. However, the contextual nature of the findings and the limited participant scope suggest that further research is needed using mixed methods and broader samples to generalize results. This study contributes to the development of culturally responsive career guidance services and supports the integration of local wisdom into educational practices.